IOT Rancang Bangun Alat Pengusir Hama Burung pada Padi Sawah Petani Berbasis Internet of Things (IoT) - Sufaat, Imam; Juliandri, Juliandri (Journal of Computer System and Informatics (JoSYC), 2024)
This research aims to develop an effective and efficient bird pest repellent tool in farmers' rice fields by utilizing Internet of Things (IoT) technology. Bird pests often pose a serious threat to agricultural products, especially in rice fields. Through the application of IoT, this tool can monitor real-time bird activity around agricultural areas and take appropriate preventive measures. This tool is designed to utilize motion sensors or pir sensors, surveillance cameras, and a sound or visual signal delivery system to chase away birds. approaching agricultural areas. PIR sensors are widely used in a variety of applications, including home security systems, motion sensor lighting, and building automation. The main advantages of PIR sensors are their low power consumption and ability to provide fast response to movement, making them an efficient and effective choice for many detection applications. motion, data collected from sensors and cameras will be sent to the IoT platform with the Telegram application and which is connected via an internet connection, allowing farmers to monitor and control tools remotely via smart devices such as smartphones or computers. The main advantage of this tool is its ability to provide a quick response to the presence of bird pests, reduce agricultural yield losses and increase crop productivity. Additionally, integration with IoT provides high flexibility and connectivity, enabling continuous system optimization. designing this tool involves the hardware and software design stages. The hardware consists of a pir sensor, an esp 32 cam microcontroller, and a speaker and servo. While the software consists of Arduino Ide, Blynk and Telegram. After design, the tool is field tested for performance. Test results show that this tool is able to detect the presence of birds with good accuracy, provides a fast response in chasing them away, Telegram is able to communicate by giving commands and receiving images, Blynk can provide information on the condition of the tool when it is online and give commands to activate the servo, sound or both of them. With a significant removal success rate, this tool is successful in reducing losses caused by bird strikes in agriculture. Additionally, it has low power consumption and can be integrated with existing IoT platforms for remote monitoring and data analysis. It is hoped that this research can make a positive contribution to efforts to develop sustainable agricultural technology and improve farmers' welfare by protecting agricultural products from bird pest attacks. Thus, it is hoped that the implementation of this tool in the field can provide an innovative and efficient solution in controlling bird pests in farmers' rice fields.